2009
DOI: 10.2478/s11534-008-0128-8
|View full text |Cite
|
Sign up to set email alerts
|

A first-principles study of π-conjugated thiol phenothiazine derivatives adsorbed on Au(111) surface

Abstract: Abstract:We present an extensive theoretical study of a series of phenothiazine derivatives adsorbed on Au(111). A series of experimentally accessible quantities are calculated (ultra-violet photoemission spectra, scanning tunneling microscopy images). All simulations were performed by using DFT techniques and LCAO expansion of the molecular orbitals. The microscopic picture established in this work provides a deeper understanding of the interfacial processes that govern the working principle of single-molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Some recent publications revealed special properties for the aggregates obtained by the deposition of phenothiazine units on gold nanoparticules via mercapto derivatives . An exhaustive theoretical investigation of single-molecule PTZ derivative absorption on Au(111) surface was presented by Morari et al They have shown that the interaction energy between the Au(111) surface and the PTZ derivative molecule with 6 different relative positions is ranking between 48.4 and 78.4 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent publications revealed special properties for the aggregates obtained by the deposition of phenothiazine units on gold nanoparticules via mercapto derivatives . An exhaustive theoretical investigation of single-molecule PTZ derivative absorption on Au(111) surface was presented by Morari et al They have shown that the interaction energy between the Au(111) surface and the PTZ derivative molecule with 6 different relative positions is ranking between 48.4 and 78.4 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%